Recent advancements in polyoxometalate-functionalized fiber materials: A review - Liang, Zhijie; Yao, Yiqing; Wang, Haifeng (Nanotechnology reviews (Berlin), 2024)
The development of advanced composite materials based on polyoxometalates (POMs) and fibers has attracted significant attention due to their combination of the unique chemical reactivity of POMs and the flexible wearable properties of fiber materials. The exceptional properties exhibited by those resultant composites have been widely employed in catalysis and optical sensors. In this article, we aim to provide an overview of progress on POMs functionalized fiber materials involving the preparation methods, namely, electrostatic spinning and layer-by-layer self-assembly methods, as well as the developments in the fields of catalysis, photochromism, and photoluminescence. Current applications are critically assessed and promising future target systems are discussed. In this review, polyoxometalate-based fiber materials, including preparation and application, are introduced, showing promising performances in catalysis and optical property.